A neighbourhood-scale estimate for the cooling potential of green roofs - Suter,I; Maksimovic,C; Van,Reeuwijk M (Urban Climate, 2017)
Green roofs offer the possibility to mitigate multiple environmental issues in an urban environment. A common benefit attributed to green roofs is the temperature reduction through evaporation. This study focuses on evaluating the effect that evaporative cooling has on outdoor air temperatures in an urban environment. An established urban energy balance model was modified to quantify the cooling potential of green roofs and study the scalability of this mitigation strategy. Simulations were performed for different climates and urban geometries, with varying soil moisture content, green roof fraction and urban surface layer thickness. All simulations show a linear relationship between surface layer temperature reduction ΔTs and domain averaged evaporation rates from vegetation mmW, i.e. ΔTs = eW ⋅ mmW, where eW is the evaporative cooling potential with a value of ∼ −0.35 Kdaymm−1. This relationship is independent of the method by which water is supplied. We also derive a simple algebraic relation for eW using a Taylor series expansion.